Is It Practical Digital Learning Application For Learning 3D Graphic Design Based on Augmented Reality? - Fitri Ayu; Ganefri Ganefri; Dedy Irfan; Asrul Huda; Des Suryani (Journal of Applied Engineering and Technological Science (JAETS), 2023)
Learning Graphic Design requires a high level of visualization, especially for design concepts or 3D interior design. If this material is only taught through guided practice in class, the learning outcomes will certainly not be optimal, especially for vocational graduates in the current digital era. The research aims to test the practicality of digital learning applications based on augmented reality technology as a learning medium for 3D interior graphic design. The type of research is Research and Development (R&D) with the Borg and Gall Method, data collection techniques using Likert scale questionnaires, applications built using Blender for modelling, Unity 3D for Augmented Reality Implementation, Android Studio for designing applications, Firebase for database storage, and Fiqma to design the interface design. This research produces a digital learning application that is used for learning 3D interior graphic design which is equipped with learning needs such as classrooms, and communication rooms and is based on Augmented Reality technology so that the resulting interior design objects can be displayed in real-time. Aiken's V formula is used to test the practicality of digital learning applications. The research results showed that the average Aiken's V score from lecturers was 85.22% in the practical category, and students in the small group test was 82.96% and students in the large group test was 83.04% in the practical category. So, it can be concluded that the use of the DiGi.AR application based on Augmented Reality is good and practical for learning 3D graphic design.